GLOMERULAR LESIONS CAUSING NEPHROTIC SYNDROME (LIGHT MICROSCOPIC FINDINGS) IN 75 ADULT PATIENTS - Haq, Najib -ul-; Mahmood, Khalid (Journal of Ayub Medical College Abbottabad, 1998)
This study includes seventy-five adult patients of Nephrotic syndrome who underwent successful Renal Biopsy in order to determine the Glomerular pathology on light microscopy. More than 90% patients had primary> glomerular lesions and the rest had secondary glomerular involvement. Focal and segmental proliferative glomerulonephritis ( 3 8 % ) and membranous glomerulonephritis (30%) were found to be the commonest lesions. Diabetes was the commonest (5%) cause of secondary glomerular lesions.